2020
DOI: 10.1038/s41467-019-14118-w
|View full text |Cite
|
Sign up to set email alerts
|

Integrated single cell analysis of blood and cerebrospinal fluid leukocytes in multiple sclerosis

Abstract: Cerebrospinal fluid (CSF) protects the central nervous system (CNS) and analyzing CSF aids the diagnosis of CNS diseases, but our understanding of CSF leukocytes remains superficial. Here, using single cell transcriptomics, we identify a specific location-associated composition and transcriptome of CSF leukocytes. Multiple sclerosis (MS) – an autoimmune disease of the CNS – increases transcriptional diversity in blood, but increases cell type diversity in CSF including a higher abundance of cytotoxic phenotype… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

32
282
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 295 publications
(335 citation statements)
references
References 79 publications
32
282
1
Order By: Relevance
“…The patterns across several sncRNA species implicate changes in the general cellular mechanisms, such as alternative splicing and mRNA translation, occurring for example during lymphocyte activation, while cytokine signaling pathways critical for T helper differentiation were more selectively modulated by miRNAs. Collectively, these observations underscore the relevance of studying the CSF compartment in a CNS disease such as MS, with CSF reflecting more closely disease processes occurring in the target organ 34 , including enrichment of encephalitogenic immune cell populations 35,36 .…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The patterns across several sncRNA species implicate changes in the general cellular mechanisms, such as alternative splicing and mRNA translation, occurring for example during lymphocyte activation, while cytokine signaling pathways critical for T helper differentiation were more selectively modulated by miRNAs. Collectively, these observations underscore the relevance of studying the CSF compartment in a CNS disease such as MS, with CSF reflecting more closely disease processes occurring in the target organ 34 , including enrichment of encephalitogenic immune cell populations 35,36 .…”
Section: Discussionmentioning
confidence: 83%
“…Conversely, changes in snoRNA-and tRNA-mediated mRNA translation mechanisms were more conspicuous in CSF cells. In MS, CSF cells preferentially include CCR7-expressing memory CD4 + T cells characterized by upregulation of genes involved in T cell activation as opposed to downregulation of genes associated with naïve cell state 36,37,57 . Our observations are in accordance with a recent single cell study comparing CSF cells and blood cells of MS patients during relapse 36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, our human CSF transcriptome analyses placed CD11c + CD88 + CD317 + cells within a population of myeloid cells that was previously defined as CSF microglia 11,[32][33][34] . We found that activated, but not naive murine microglia concomitantly express CD11c, CD88, and CD317.…”
Section: Discussionmentioning
confidence: 87%
“…Characteristic gene expression markers were employed to assign cellular identities to each cluster of myeloid populations in blood (Figure 5A) and CSF (Figure 5B). Recent studies identified myeloid cells within the CSF using scRNA-seq that resembled microglia 11,[32][33][34] , which are characterized by the expression of signature genes including CX3CR1, CSF1R, SLC2A5, MARCKS, and P2RY13 [35][36][37] .…”
Section: And Csf By Transcriptomic Profilingmentioning
confidence: 99%